A Tale's blade: Understanding evolutionary features of oviposition behavior based on Tettigoniidae (Insecta, Orthoptera, Ensifera) ovipositor morphology - Barbosa, Diego N.; Fianco, Marcos (Arthropod structure & development, 2024)
A remarkable characteristic of katydids (Orthoptera, Tettigoniidae) is the elongated ovipositor, which is associated with oviposition behavior. The high degree of complexity of both sclerites and muscles arrangement of the ovipositor, is only similar to the ovipositor of Hymenoptera. Here we describe the morphology of the ovipositor within Tettigoniidae, and add descriptions of known oviposition behavior. Fifteen skeletal structures can be recognized, of these, three pairs of muscles are new while nine pairs were already described in the literature. The new muscles are ap2vf, anterior projection of second valvifer; bcov, blade complex of the ovipositor; and dbl, dorsal blade. The morphology of the ovipositor blade complex (bcov), the shape of the first valvifer (1vf), posterior intervalvular sclerite (piv), tergite IX (T9), anterior projection of the second valvifer (ap2vf), and the second valvifer (2vf), and their related muscles affect oviposition in Tettigoniidae. This contribution helps to understand katydid's oviposition behavior. Additionally, the new descriptions help in the search for new characters in Tettigoniidae. •This work is focused in better understand the ovipositor of katydids, which is associated with the oviposition behavior.•We explored the morphology of the ovipositor within Tettigoniidae, including all known oviposition habits.•15 skeletal structures were recognized, from this, three described as new, and nine pairs of muscles.•We related the morphology of sclerites and muscles to oviposition habits.•This contribution can help to understand the evolutionary features of katydid's oviposition behavior.